Resin hemoperfusion for acute pentobarbital poisoning in rats and rabbits - LU Zhao-nian; CAI Zhu-hui; WU Zhao-guang (Acta Pharmacologica Sinica, 2016)
Hemoperfusion with domestic neutral resins (styrene divinylbenzene copolymers) for acute pentobarbital intoxication was carried out in rats. Resin Ad-1 and 2400-8 increased the numbers of awakened rats and survived rats. Duration of coma was shortened. Acute pentobarbital poisoning was established in rabbits to compare the clearance efficiency of different resins as well as activated charcoal. Blood pentobarbital levels decreased efficiently after hemoperfusion with resins and clearance for pentobarbital was consistenly greater than with uncoated activated granular charcoal. These results suggest that hemoperfusion with blood-compatible resins may be the treatment of choice in patients severely intoxicated with sedatives or hypnotics.